Strategi Kreatif Penulisan Artikel Fiksi Berbantuan ChatGPT: Studi Kualitatif pada Blogger Kompasiana di Kota Semarang - Isna Rosiana Dewi; Viro Dharma Saputra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine creative strategies for fiction writing involving collaboration between humans and AI (ChatGPT) in the Kompasiana blogger community in Semarang. Using a qualitative approach, this study collected data through in-depth interviews with four informants active in AI-assisted fiction writing. The interviews revealed a shift in the role of AI, where AI no longer functions solely as a technical tool but rather as an imaginative partner collaborating with writers in the creative process. During the writing process, writers negotiated with AI regarding style and story structure, and reflected deeply on their creative process. They also faced ethical dilemmas, particularly regarding the originality and authenticity of their work, arising from the use of AI technology. While AI writers provided new ideas and inspiration, they also demanded further considerations regarding copyright and author credibility. These findings were analyzed using the theories of Extended Mind, Distributed Cognition, and Reflective Practice to understand the dynamics of human-machine interaction in a creative context. This study proposes a dialectical and symbiotic model of creative interaction, in which writers and AI influence each other in producing fictional works. This model emphasizes that AI-assisted fiction writing is not just about efficiency in producing work, but also a process of redefining creative agency. This research demonstrates how human-machine collaboration in digital literacy can change our perspective on creative roles and ethics in the world of writing. Furthermore, this research explores the impact of AI use on the learning process of writers within the blogging community. AI, in this case ChatGPT, not only contributes to the final product but also plays a role in broadening the writer's insight into writing techniques, idea exploration, and character development.